2019
DOI: 10.1016/j.biortech.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical pretreatment of lignocelluloses for enhanced biogas production: Methane yield prediction from biomass structural components

Abstract: In this study, mechanical pretreatment was applied to six different lignocelluloses in two different treatment phases and the prediction of their methane yield was done from biomass chemical composition. Physicochemical, proximate and microbial analyses were carried out on both pretreated and untreated biomass using standard methods. Mechanical pretreatments caused the breakdown of structural materials in all the used biomass which was characterized by reduction of the lagging time during anaerobic digestion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 44 publications
(46 reference statements)
2
31
0
Order By: Relevance
“…The size reduction of lignocellulosic biomass is an essential step to increase the accessible surface area and the porosity of the particles, besides reducing the crystallinity of the cellulose and improves the efficiency of the next processing step and global production chain [63]. One advantage of mechanical pretreatment is that it does not produce any secondary inhibitory substances, which suggest that could be suitable for methane production or any other bioprocess [64]. Dahunsi [64] reported that mechanical pretreatment applied to six different lignocelluloses caused breakdown of structural material and increased the methane yield up to 22%.…”
Section: Mechanicalmentioning
confidence: 99%
See 2 more Smart Citations
“…The size reduction of lignocellulosic biomass is an essential step to increase the accessible surface area and the porosity of the particles, besides reducing the crystallinity of the cellulose and improves the efficiency of the next processing step and global production chain [63]. One advantage of mechanical pretreatment is that it does not produce any secondary inhibitory substances, which suggest that could be suitable for methane production or any other bioprocess [64]. Dahunsi [64] reported that mechanical pretreatment applied to six different lignocelluloses caused breakdown of structural material and increased the methane yield up to 22%.…”
Section: Mechanicalmentioning
confidence: 99%
“…One advantage of mechanical pretreatment is that it does not produce any secondary inhibitory substances, which suggest that could be suitable for methane production or any other bioprocess [64]. Dahunsi [64] reported that mechanical pretreatment applied to six different lignocelluloses caused breakdown of structural material and increased the methane yield up to 22%. However, it is observed that excessive size reduction of lignocellulosic biomass can lead to a lower efficiency of methane production [61].…”
Section: Mechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Other available data reports an enhancement between 15% and 45% using different mechanical devices with manure fibers as substrate at laboratory-scale [15]. Dahunsi [40] found an average improvement of 22% of the BMP on different types of lignocellulosic substrates. Overall, the substrate biodegradability with mechanical pretreatments application depends on different factors such as the substrate nature and mechanical devices and their specificities.…”
Section: Effect Of Mechanical Pretreatments On Biochemical Characterimentioning
confidence: 96%
“…AD is a process whose course largely depends on the presence of microorganisms in systems of reactors . To avoid stress affecting microorganisms present in a bioreactor induced by high concentrations of inhibitors (nitrates, heavy metals, sulfates, access of oxygen, hardly biodegradable lignocellulose compounds), a possible solution applied to intensify biogas production is to supplement the substrate fed to a bioreactor with microorganisms tolerant to unfavorable conditions, which can support the efficiency of methane fermentation …”
Section: Feedstocks Technologies and Factors Design To Intensify Bimentioning
confidence: 99%